Integrating democracy learning and prophetic social studies at Baitusalam Islamic School Yogyakarta - Nasiwan, Nasiwan; Wulandari, Taat; Wijayanti, Agustina Tri (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
This paper describes an attempt to integrate Islamic and scientific values into social studies education with the aim of developing prophetic social science theory to explain social problems from this perspective. The study focuses on the implementation of this theory at Baitusalam Islamic School in Yogyakarta, using qualitative research methods such as observation, interviews, and documentation. The findings suggest that social studies learning  Islamic values that develop boarding power, with the learning process incorporating these values into planning, implementation, and assessment. However, the study also identifies challenges in the integration process, such as the lack of student textbook references that integrate values into Islamic language for each material, insufficient learning media, and inadequate infrastructure in schools. Overall, this study highlights the importance of integrating Islamic and scientific values into social studies education to develop young people's sense of nationalism, independence, and character, while acknowledging the need to address these challenges for effective implementation.